1999
DOI: 10.1016/s0735-1097(99)00312-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orally active prostacyclin analogue on survival of outpatients with primary pulmonary hypertension

Abstract: The oral administration of BPS may have beneficial effects on the survival of outpatients with PPH as compared with conventional therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
104
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(107 citation statements)
references
References 22 publications
0
104
0
3
Order By: Relevance
“…Initial trials have shown an improvement in 6MWT, functional class and survival. 47,48 In the RCT reported by Galie et al, there was significant improvement in exercise capacity at 12 weeks. 49 However, the data from Barst et al showed no difference in 6MWT distance with oral beraprost compared to placebo at 12 months follow-up, although improvement was observed at 3 and 6 months.…”
Section: Sodium Beraprostmentioning
confidence: 97%
“…Initial trials have shown an improvement in 6MWT, functional class and survival. 47,48 In the RCT reported by Galie et al, there was significant improvement in exercise capacity at 12 weeks. 49 However, the data from Barst et al showed no difference in 6MWT distance with oral beraprost compared to placebo at 12 months follow-up, although improvement was observed at 3 and 6 months.…”
Section: Sodium Beraprostmentioning
confidence: 97%
“…Defects in hIP receptor structure and function caused by such naturally occurring mutations may ultimately lead to explanations concerning the intrinsic differences observed in the pathophysiology of cardiovascular disease and responses to therapy (e.g. variable responses to iloprost in the treatment of pulmonary hypertension) (19,20). In this study, we characterize the effects of the V25M and R212H polymorphisms on hIP function.…”
Section: Fig 2 Competition Binding For Hip1d4pmt4 V25m and R212hmentioning
confidence: 98%
“…Oral beraprost has been licensed in Japan for PPH after a controlled study in 58 patients showed evidence for increased survival in patients with PPH treated with beraprost, compared to conventional treatment [46]. There is, however, no sufficient data on the long-term efficacy of beraprost and there is also no information about the use of beraprost in patients with collagen vascular disease.…”
Section: Treatmentmentioning
confidence: 99%